Proceedings of the 4th ACM SIGCOMM Conference on Internet Measurement 2004
DOI: 10.1145/1028788.1028838
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of spam traffic and the use of DNS black lists

Abstract: This paper presents quantitative data about SMTP traffic to MIT's Computer Science and Artificial Intelligence Laboratory (CSAIL) based on packet traces taken in December 2000 and February 2004. These traces show that the volume of email has increased by 866% between 2000 and 2004. Local mail hosts utilizing black lists generated over 470,000 DNS lookups, which accounts for 14% of all DNS lookups that were observed on the border gateway of CSAIL on a given day in 2004. In comparison, DNS black list lookups acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(92 citation statements)
references
References 3 publications
0
89
1
2
Order By: Relevance
“…In [13], Jung and Sit check the use of DNS blacklists for address-based filtering of spams. There are some advantages and disadvantages of whitelists and blacklists.…”
Section: Related Workmentioning
confidence: 99%
“…In [13], Jung and Sit check the use of DNS blacklists for address-based filtering of spams. There are some advantages and disadvantages of whitelists and blacklists.…”
Section: Related Workmentioning
confidence: 99%
“…Blacklisting is the most commonly used technique. Back in 2004, Jung and Sit observed that 80% of the identified spam sources of their dataset were found in at least one DNS blacklist [11]. However, Ramachandran et al showed in [16] that DNS-based blacklists cannot keep up with bots, which is the main source of today's spamming activity.…”
Section: B Network-level Mitigation Techniquesmentioning
confidence: 99%
“…There is a prediction that the spam will be 70% of the email traffic in 2007 [1]. There are lot of source filters are available in real time.…”
Section: Source Filtersmentioning
confidence: 99%
“…Even if one DNS black list is out of service the mail server can manage with other lists. In recent days the DNSBL lookups are increased tremendously of total DNS lookups compared to 5 years before [1]. Nearly 80% of the spam generated by relays that appear in one at least one of eight major blacklists [4].…”
Section: Bayesian Filtermentioning
confidence: 99%
See 1 more Smart Citation